Innovation ecosystems and measures aimed at environmental sustainability: Cidade Pedra Branca case study - Aguiar Dutra, Ana Regina; Silva, Evellyn Sperber; Cubas, Anelise Leal Vieira (Interações, 2019)
The proposal described herein is aimed at technological innovation, with a focus on product sustainability. The object of this study was six companies from the innovation ecosystem Cidade Pedra Branca, which sought to identify socio-environmental actions that also have the goal of generating significant results in economic terms. We concluded that, in general, the companies in Cidade Pedra Branca are committed to achieving social, environmental, and economic sustainability.